Lily's mistake eaudiobook with loving drake. - Ann, Pamela (It's Always Been You, 2014)
Lily Alexander had always been in love with Drake Tatum, even before she knew what love meant. One fateful night during one of their family vacations, Lily gave her virginity to Drake. After that magical night, Drake and Lily avoided each other successfully for eight years. However, due to their parents' meddling, the two suddenly found themselves working side by side. Sparks fly. Their eyes devour each other. The sudden impact of being in each other's orbit was electrifying. Drake wants to consume Lily almost immediately. But to what extent? Will Lily surrender again to the man who once broke her heart? Contains mature themes.